PERKEMBANGAN PEMANFAATAN PLTS DI DKI JAKARTA MENUJU TARGET 13,8 MW TAHUN 2025 - Junior, Simon; Satya Kumara, I Nyoman; Dwi Giriantari, Ida Ayu (Jurnal SPEKTRUM; Vol 9 No 1 (2022): Jurnal SPEKTRUM, 2022)
PLTS is one of the solutions to produce electrical energy that can save electricity payment rates and has a good impact on the surrounding environment. This study aims to analyze the development of PLTS utilization in DKI Jakarta, types and total PLTS found in DKI Jakarta. This research was conducted by collecting data from journals, articles and news on the internet in the form of PLTS data in DKI Jakarta, type and capacity of PLTS, year of operation, location, ownership status and institutions that built PLTS. Then from the data, a review is carried out regarding the number, location, and total capacity of the PLTS built every year, the results of this study are the number of PLTS in DKI Jakarta is 124 units with a total capacity of 11,088 kWp, with rooftop PLTS totaling 119 PLTS units. with a capacity of 10,29 MW and PLTS Ground-mount as many as 5 units with a PLTS capacity of 0,8 MW. The PLTS development in DKI Jakarta has met the RUEN target of 73% to reach the 13.8 MW target in 2025.